IMPLEMENTASI ALAT PERAGA OPERASI BILANGAN BULAT BAGI GURU SEKOLAH DASAR (SD) SE-KECAMATAN ILIR BARAT I PALEMBANG - Putri, Ratu Ilma Indra (Mathematics Education Journal, 2011)
The purpose of this activity is to increase the ability of teachers in 1) make mathematics manipulative as a media of operations of integer, 2) used mathematics manipulative is made in classroom simulation. Method of the activities performed is a demonstration, presentations and discussion. The participants of this activity are 25 teachers of “Kecamatan Ilir Barat I" Palembang. The results of the activities showed that, 95% of teachers are involved in each mathematics activities, discussions, and simulations. The results of pre test and post test showed that there is increasing ability of mathematics teachers in “Kecamatan Ilir Barat I” Palembang. The results of questionnaire showed that 100% of participants felt very satisfied follow the given activities and want the existence of a follow-up activity.DOI: 10.22342/jpm.5.1.823